Cancer Immunotherapy Paradigms, Practice and Promise - Curiel, Tyler J. (Springer New York : Imprint: Springer, 2013)
This volume is a comprehensive discussion of the major factors affecting tumor immunology and a discussion of all major anti-cancer immunotherapeutic agents approved by the Food and Drug Administration of the United States and by European agencies. Many promising but unapproved agents in clinical trials are also discussed, as are key pre-clinical developments. The major challenges and intellectual issues facing investigators developing novel immunotherapeutics are discussed in detail as are conceptual developments influencing current and future treatment strategies. Each chapter begins by defining all relevant key terms and concepts and provides pertinent background information so that the text will be accessible to newcomers to the field as well as to the expert. This text book should provide an excellent reference resource for investigators in tumor immunology, life sciences students, drug developers designing novel anti-cancer immunotherapeutics, and to other individuals with some scientific training wishing to gain a better understanding of the field of tumor immunotherapy. Although the field is evolving rapidly, we have taken pains to ensure that information was as up to date as possible as the text went to press.